Preparation method of photocatalytic degradation material for treating acidic chrome blue K sewage
By loading polyindole-3 carbonylformamide and synthesized polybistrifluoromethylstyrene on the surface of the foamed iron matrix, the cobalt coordination polymer was formed, and the problems of low degradation rate and poor reusability of existing photocatalytic degradation materials were solved, and efficient and stable acidic chromium blue K sewage treatment was achieved.
Patent Information
- Application Number
- CN202510027573.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The existing photocatalytic degradation materials have low degradation rates when treating acidic chromium blue K sewage, and their reusability is not ideal, making it difficult to meet actual needs.
Polyindol-3 carbonylformamide is supported on the surface of the foamed iron matrix and polybistrifluoromethylstyrene is synthesized to form a polyindol-3 carbonylformamide/polybistrifluoromethylstyrene-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-cobalt-co
The prepared photocatalytic degradation materials have high efficiency and excellent photocatalytic performance and excellent reuse stability, and can effectively degrade acidic chromium blue K sewage to meet actual needs.
Smart Images

Figure CN119819370A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of acidic chrome blue K-containing sewage treatment, in particular to a method for preparing a photocatalytic degradation material for treating acidic chrome blue K sewage. Background Art
[0002] Azo dyes are dyes with the largest number and variety of azo groups. Acid chrome blue K, as an azo dye, is widely used in metallurgical industry analysis, soil and water analysis, and plant analysis of agricultural and forestry crops. When acid chrome blue K comes into contact with the human body or enters the human body through the food chain, the azo group will break and produce carcinogenic and harmful substances, which will have serious consequences such as carcinogenicity, teratogenicity and mutagenicity. Acid chrome blue K mainly poses a direct threat to humans and the environment by entering the water environment to form acid chrome blue K wastewater. Therefore, it is of great significance to effectively treat acid chrome blue K wastewater.
[0003] Traditional methods for treating organic pollutants in sewage include chemical oxidation, flocculation and precipitation, and electrochemical methods. Chemical oxidation and flocculation and precipitation processes require the addition of chemical reagents, which will produce secondary pollution. Electrochemical organic sewage treatment processes require the consumption of electrical energy, and the electrode materials have a limited degradation rate for acid chrome blue K. Photocatalytic degradation of organic pollutants refers to the generation of photogenerated electrons and holes by photocatalytic degradation materials during illumination. Photogenerated electrons and holes can produce free radicals, thereby achieving the degradation of organic pollutants. Photocatalytic degradation is the development direction of green and environmentally friendly treatment technology for acid chrome blue K sewage.
[0004] However, currently in the field of acid chrome blue K wastewater treatment, the degradation rate of photocatalytic degradation materials is not high and the reusability is not ideal, which makes it difficult to meet the actual requirements of photocatalytic degradation of acid chrome blue K wastewater. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a photocatalytic degradation material for treating acidic chrome blue K wastewater. The photocatalytic degradation material prepared by the method has high efficiency and excellent photocatalytic performance, and has excellent repeated use stability, and can meet the actual requirements for photocatalytic degradation of acidic chrome blue K wastewater.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] The present invention provides a method for preparing a photocatalytic degradation material for treating acidic chrome blue K wastewater, comprising the following steps:
[0008] Step [1]: loading polyindole-3-carbonylformamide on the surface of the foamed iron matrix;
[0009] Step [2] synthesizing poly(trifluoromethylstyrene);
[0010] Step [3] converts the polyindole-3-carbonylformamide on the surface of the foamed iron matrix into a polyindole-3-carbonylformamide / poly(trifluoromethylstyrene) cobalt coordination polymer.
[0011] Preferably, the step [1] specifically includes the following operations:
[0012] a1. Add indole-3-carboxylic acid methyl ester, 1H-indole-3-carboxamide and tert-butyl peroxybenzoate to dimethyl sulfoxide and mix to form a base solution; add ammonium persulfate to deionized water and mix to form an additive solution; mix the base solution and the additive solution in a certain proportion to form a synthetic solution, react at room temperature for 14 to 18 hours, filter the solid product, wash with deionized water, and dry at room temperature for 10 to 12 hours to obtain a solid reactant polyindole-3 carbonyl formamide;
[0013] a2. Add polyindole-3-carbonylformamide, 5-indolecarboxylic acid, ammonium persulfate and ferric acetate to deionized water, mix to form an electrodeposition solution, disperse by ultrasonic wave for 0.5 to 1 hour, immerse the foamed iron sample in the electrodeposition solution and use it as cathode, use stainless steel electrode as anode, and electrodeposit at room temperature at a constant voltage of -1.0V to -1.5V for 40 to 60 minutes to obtain foamed iron with polyindole-3-carbonylformamide loaded on the surface, which is recorded as intermediate A.
[0014] Preferably, in step a1, the amount of indole-3-carboxylic acid methyl ester added to each liter of the base liquid is 40-70 g, the amount of 1H-indole-3-carboxamide added is 80-110 g, and the amount of tert-butyl perbenzoate added is 5-30 mL; the concentration of ammonium persulfate in the additive liquid is 20-40 g / L; and the volume ratio between the base liquid and the additive liquid in the synthetic liquid is 8-11:1-3.
[0015] Preferably, in step a2, the amount of polyindole-3-carbonylformamide added to each liter of the electrodeposition solution is 110-140 g, the amount of 5-indolecarboxylic acid added is 20-40 g, the amount of ammonium persulfate added is 5-20 g, and the amount of ferric acetate added is 30-60 g; the weight of the foamed iron immersed in each liter of the electrodeposition solution is 110-140 g.
[0016] Preferably, the step [2] specifically includes the following operations:
[0017] b1. Add 3,5-bis(trifluoromethyl)styrene to dimethyl sulfoxide and mix to form a reaction solution; add titanocene dichloride and lauroyl peroxide to chloroform and mix to form a catalyst solution;
[0018] b2. Add a certain amount of catalyst liquid to the reaction solution, react at room temperature for 24-28 hours, filter the solid phase product, wash with acetone and then with deionized water, and dry at room temperature for 8-10 hours to obtain poly(trifluoromethylstyrene).
[0019] Preferably, in step b1, the amount of 3,5-bis(trifluoromethyl)styrene added to each liter of the reaction solution is 90-130 g; the amount of titanocene dichloride added to each liter of the catalyst solution is 5-15 g, and the amount of lauroyl peroxide added to each liter of the catalyst solution is 2-8 g.
[0020] Preferably, in step b2, the volume ratio between the catalytic liquid and the reaction liquid is 2-5:13-19.
[0021] Preferably, the step [3] specifically includes the following operations:
[0022] c1. Adding cobalt bromide, urea, ammonium bifluoride and the poly(trifluoromethylstyrene) to deionized water and mixing to form a coordination polymer solution;
[0023] c2. Immerse the intermediate A in the coordination polymer formation liquid, heat it in a water bath to 40-60°C, react for 24-30 hours, take out the foamed iron sample, and dry it for 4-6 hours at room temperature under the protection of a nitrogen atmosphere to obtain a foamed iron with a surface loaded with polyindole-3-carbonylformamide / polybis(trifluoromethylstyrene) cobalt coordination polymer, i.e., the photocatalytic degradation material.
[0024] Preferably, in step c1, the amount of cobalt bromide added to each liter of the coordination polymer forming liquid is 150-190 g, the amount of urea added is 30-45 g, the amount of ammonium bifluoride added is 20-70 g, and the amount of polybis(trifluoromethylstyrene) added is 80-130 g.
[0025] Preferably, in step c2, the weight of the intermediate A immersed in each liter of the coordination polymer forming liquid is 60-90 g.
[0026] Positive effects of the present invention: The photocatalytic degradation material prepared by the method of the present invention has a polyindole-3-carbonylformamide / polybis(trifluoromethylstyrene) cobalt coordination polymer loaded on the surface of the foamed iron, which is formed by hydrogen bonds between the imino group of polyindole-3-carbonylformamide and the fluoride ion of polybis(trifluoromethylstyrene), thereby forming a coordination polymer ligand, which forms a polyindole-3-carbonylformamide / polybis(trifluoromethylstyrene) cobalt coordination polymer with cobalt on the surface of the foamed iron matrix; wherein each cobalt ion forms six coordination bonds with the six fluoride ions of the coordination polymer ligand. Based on the above structural characteristics, the coordination polymer forms a delocalized π bond, is a coordination polymer with a narrow band gap, and is conducive to the generation of photogenerated electrons and photogenerated holes; at the same time, the bipolaron behavior characteristics of the coordination polymer promote the transmission of photogenerated holes and photogenerated electrons. In addition, the foamed iron-based polyindole-3-carbonylformamide / polybis(trifluoromethylstyrene) cobalt coordination polymer not only has a large effective activation area, but also can effectively realize the physical and chemical adsorption of acid chrome blue K at the activated position on its surface; the prepared photocatalytic degradation material can also effectively inhibit the recombination of photogenerated electrons and photogenerated holes, and in the process of acid chrome blue K wastewater treatment, it can generate sufficient highly active free radicals to degrade acid chrome blue K.
[0027] In conclusion, the photocatalytic degradation material prepared according to the present invention has high-efficiency and excellent photocatalytic performance and excellent repeated use stability, and can meet the actual requirements for photocatalytic degradation of acidic chrome blue K wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the preparation process of the photocatalytic degradation material of the present invention;
[0029] Figure 2 is a schematic diagram of the microstructure of the photocatalytic degradation material of the present invention;
[0030] Figure 3 is the relative concentration of residual acid chrome blue K in the simulated acid chrome blue K-containing wastewater treated in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;
[0031] Figure 4 It is a relationship diagram between the number of times of use and the relative concentration of residual acid chrome blue K when Example 1, Comparative Example 1 and Comparative Example 2 are repeatedly used to treat simulated acid chrome blue K-containing sewage under visible light irradiation;
[0032] Figure 5 It is a relationship diagram between the number of times of use and the relative concentration of residual acid chrome blue K when Example 1, Comparative Example 1 and Comparative Example 2 are repeatedly used to treat simulated acid chrome blue K-containing wastewater under ultraviolet light irradiation. DETAILED DESCRIPTION
[0033] Reference Figure 1The present invention provides a method for preparing a photocatalytic degradation material for treating acidic chrome blue K wastewater, comprising the following steps:
[0034] Step [1] loading polyindole-3-carbonylformamide on the surface of the foamed iron matrix specifically comprises the following operations:
[0035] a1. Add indole-3-carboxylic acid methyl ester, 1H-indole-3-carboxamide and tert-butyl perbenzoate to dimethyl sulfoxide and mix to form a base solution, wherein the amount of indole-3-carboxylic acid methyl ester added per liter of the base solution is 40 to 70 g, the amount of 1H-indole-3-carboxamide added is 80 to 110 g, and the amount of tert-butyl perbenzoate added is 5 to 30 mL; ammonium persulfate is added to deionized water and mixed to form an ammonium sulfate concentration of 20 to 40 g / L of the additive solution; the base liquid and the additive solution are mixed in a ratio of 8 to 11:1 to 3 between the volume ratio of the base liquid and the additive solution to form a synthetic solution, react at room temperature for 14 to 18 hours, filter the solid phase product, wash with deionized water, and dry at room temperature for 10 to 12 hours to obtain a solid reactant polyindole-3 carbonyl formamide, wherein the structural formula of the polyindole-3 carbonyl formamide is:
[0036]
[0037] a2. Add polyindole-3-carbonylformamide, 5-indolecarboxylic acid, ammonium persulfate and ferric acetate to deionized water and mix to form an electrodeposition solution (the amount of polyindole-3-carbonylformamide added per liter of the electrodeposition solution is 110-140 g, the amount of 5-indolecarboxylic acid added is 20-40 g, the amount of ammonium persulfate added is 5-20 g, and the amount of ferric acetate added is 30-60 g), and ultrasonic dispersion is performed for 0.5 to 1 hour. The foamed iron sample is immersed in the electrodeposition solution and used as a cathode (the weight of the foamed iron immersed in the electrodeposition solution per liter is 110-140 g), a stainless steel electrode is used as an anode, and electrodeposition is performed at a constant voltage of -1.0 V to -1.5 V at room temperature for 40-60 minutes to obtain a foamed iron loaded with polyindole-3-carbonylformamide on the surface, which is recorded as intermediate A.
[0038] Step [2] synthesizing polybis(trifluoromethylstyrene), specifically comprising the following operations:
[0039] b1. Add 3,5-bis(trifluoromethyl)styrene to dimethyl sulfoxide and mix to form a reaction solution, wherein the amount of 3,5-bis(trifluoromethyl)styrene added to each liter of the reaction solution is 90 to 130 g; add dichlorotitacenes and lauroyl peroxide to chloroform and mix to form a catalyst solution, wherein the amount of dichlorotitacenes added to each liter of the catalyst solution is 5 to 15 g, and the amount of lauroyl peroxide added is 2 to 8 g;
[0040] b2. A certain amount of catalyst liquid is added to the reaction liquid (the volume ratio between the catalyst liquid and the reaction liquid is 2 to 5:13 to 19), and the reaction is carried out at room temperature for 24 to 28 hours. The solid phase product is filtered, washed with acetone and then with deionized water, and dried at room temperature for 8 to 10 hours to obtain polybis(trifluoromethylstyrene), whose structural formula is:
[0041]
[0042] Step [3] converting the polyindole-3-carbonylformamide on the surface of the foamed iron substrate into a polyindole-3-carbonylformamide / poly(trifluoromethylstyrene) cobalt coordination polymer, specifically comprising the following operations:
[0043] c1. Adding cobalt bromide, urea, ammonium bifluoride and the polybis(trifluoromethyl)styrene to deionized water, mixing to form a coordination polymer forming liquid, wherein the amount of cobalt bromide added per liter of the coordination polymer forming liquid is 150 to 190 g, the amount of urea added is 30 to 45 g, the amount of ammonium bifluoride added is 20 to 70 g, and the amount of polybis(trifluoromethyl)styrene added is 80 to 130 g;
[0044] c2. The intermediate A is immersed in the coordination polymer forming liquid (the weight of the intermediate A immersed in each liter of the coordination polymer forming liquid is 60-90g), heated to 40-60°C in a water bath, reacted for 24-30 hours, and the foamed iron sample is taken out and dried at room temperature under nitrogen atmosphere for 4-6 hours to obtain a foamed iron with a surface loaded with polyindole-3-carbonylformamide / polybis(trifluoromethylstyrene)-cobalt coordination polymer, i.e., the photocatalytic degradation material (foamed iron-based polyindole-3-carbonylformamide / polybis(trifluoromethylstyrene)-cobalt coordination polymer), the microstructure schematic diagram of which is shown as follows Figure 2 As shown, the structural formula of the polyindole-3-carbonylformamide / polybis(trifluoromethylstyrene) cobalt coordination polymer is:
[0045]
[0046] The preferred embodiments of the present invention are described below by way of example.
[0047] Example 1
[0048] Preferred embodiment 1 of the present invention provides a method for preparing a photocatalytic degradation material for treating acidic chrome blue K wastewater, comprising the following steps:
[0049] Step [1] loading polyindole-3-carbonylformamide on the surface of the foamed iron matrix specifically comprises the following operations:
[0050] a1. Indole-3-carboxylic acid methyl ester, 1H-indole-3-carboxamide and tert-butyl perbenzoate were added to dimethyl sulfoxide and mixed to form a base solution, wherein the amount of indole-3-carboxylic acid methyl ester added per liter of the base solution was 60 g, 1H-indole-3-carboxamide was added in an amount of 90 g, and tert-butyl perbenzoate was added in an amount of 20 mL; ammonium persulfate was added to deionized water and mixed to form an ammonium sulfate concentration of 35 g / L of the additive solution; the base liquid and the additive solution were mixed in a ratio of 8:1 between the volume ratio of the base liquid and the additive solution to form a synthetic solution, reacted at room temperature for 15 hours, the solid phase product was filtered, washed with deionized water, and dried at room temperature for 12 hours to obtain a solid reactant polyindole-3 carbonyl formamide;
[0051] a2. Add polyindole-3-carbonylformamide, 5-indolecarboxylic acid, ammonium persulfate and ferric acetate to deionized water, mix to form an electrodeposition solution (polyindole-3-carbonylformamide added in an amount of 130 g, 5-indolecarboxylic acid added in an amount of 30 g, ammonium persulfate added in an amount of 15 g, and ferric acetate added in an amount of 50 g per liter of the electrodeposition solution), disperse with ultrasound for 1 hour, immerse the foamed iron sample in the electrodeposition solution and use it as a cathode (the weight of the foamed iron immersed in the electrodeposition solution per liter is 120 g), use a stainless steel electrode as an anode, and electrodeposit at room temperature at a constant voltage of -1.4 V for 50 minutes to obtain a foamed iron with polyindole-3-carbonylformamide on its surface, which is recorded as intermediate A.
[0052] Step [2] synthesizing polybis(trifluoromethylstyrene), specifically comprising the following operations:
[0053] b1. 3,5-bis(trifluoromethyl)styrene was added to dimethyl sulfoxide and mixed to form a reaction solution, wherein 3,5-bis(trifluoromethyl)styrene was added in an amount of 100 g per liter of the reaction solution; dichlorotitacenes and lauroyl peroxide were added to chloroform and mixed to form a catalyst solution, wherein dichlorotitacenes were added in an amount of 10 and lauroyl peroxide was added in an amount of 7 g per liter of the catalyst solution;
[0054] b2. A certain amount of catalyst liquid was added to the reaction liquid (the volume ratio between the catalyst liquid and the reaction liquid was 2:13), and the reaction was carried out at room temperature for 25 hours. The solid phase product was filtered, washed with acetone and then with deionized water, and dried at room temperature for 9 hours to obtain poly(trifluoromethylstyrene).
[0055] Step [3] converting the polyindole-3-carbonylformamide on the surface of the foamed iron substrate into a polyindole-3-carbonylformamide / poly(trifluoromethylstyrene) cobalt coordination polymer, specifically comprising the following operations:
[0056] c1. Adding cobalt bromide, urea, ammonium bifluoride and the polybis(trifluoromethylstyrene) to deionized water, mixing to form a coordination polymer forming liquid, wherein the amount of cobalt bromide added per liter of the coordination polymer forming liquid is 160 g, the amount of urea added is 35 g, the amount of ammonium bifluoride added is 50 g, and the amount of polybis(trifluoromethylstyrene) added is 120 g;
[0057] c2. Immerse the intermediate A in the coordination polymer forming liquid (the weight of the intermediate A immersed in each liter of the coordination polymer forming liquid is 80g), heat it to 50°C in a water bath, react for 28 hours, take out the foamed iron sample, and dry it at room temperature under the protection of a nitrogen atmosphere for 5 hours to obtain a foamed iron with a surface loaded with polyindole-3-carbonylformamide / polybis(trifluoromethylstyrene) cobalt coordination polymer, i.e., the photocatalytic degradation material (foamed iron-based polyindole-3-carbonylformamide / polybis(trifluoromethylstyrene) cobalt coordination polymer), recorded as Example 1.
[0058] Comparative Example 1
[0059] This comparative example 1 provides a method for preparing a photocatalytic degradation material for treating acidic chrome blue K wastewater, comprising the following steps:
[0060] Step [1] loading polyindole-3-carbonylformamide on the surface of the foamed iron matrix specifically comprises the following operations:
[0061] a1. Indole-3-carboxylic acid methyl ester, 1H-indole-3-carboxamide and tert-butyl perbenzoate were added to dimethyl sulfoxide and mixed to form a base solution, wherein the amount of indole-3-carboxylic acid methyl ester added per liter of the base solution was 50 g, 1H-indole-3-carboxamide was added in an amount of 100 g, and tert-butyl perbenzoate was added in an amount of 10 mL; ammonium persulfate was added to deionized water and mixed to form an ammonium sulfate concentration of 30 g / L of the additive solution; the base liquid and the additive solution were mixed in a ratio of 9:2 in a volume ratio to form a synthetic solution, reacted at room temperature for 15 hours, the solid phase product was filtered, washed with deionized water, and dried at room temperature for 10 hours to obtain a solid reactant polyindole-3 carbonyl formamide;
[0062] a2. Polyindole-3-carbonylformamide, 5-indolecarboxylic acid, ammonium persulfate and ferric acetate were added to deionized water and mixed to form an electrodeposition solution (polyindole-3-carbonylformamide was added in an amount of 130 g per liter of the electrodeposition solution, 5-indolecarboxylic acid was added in an amount of 30 g, ammonium persulfate was added in an amount of 10 g, and ferric acetate was added in an amount of 40 g), and ultrasonic dispersion was performed for 1 hour, the foamed iron sample was immersed in the electrodeposition solution and used as a cathode (the weight of the foamed iron immersed in the electrodeposition solution per liter was 130 g), a stainless steel electrode was used as an anode, and a constant voltage of -1.0 V to -1.5 V was used for electrodeposition for 40-60 minutes at room temperature to obtain a foamed iron having a surface load of polyindole-3-carbonylformamide, which was recorded as Comparative Example 1.
[0063] Comparative Example 2
[0064] This comparative example 2 provides a method for preparing a photocatalytic degradation material for treating acidic chrome blue K wastewater, comprising the following steps:
[0065] Step [1] loading polyindole-3-carbonylformamide on the surface of the foamed iron matrix specifically comprises the following operations:
[0066] a1. Indole-3-carboxylic acid methyl ester, 1H-indole-3-carboxamide and tert-butyl perbenzoate were added to dimethyl sulfoxide and mixed to form a base solution, wherein the amount of indole-3-carboxylic acid methyl ester added per liter of the base solution was 60 g, 1H-indole-3-carboxamide was added in an amount of 90 g, and tert-butyl perbenzoate was added in an amount of 15 mL; ammonium persulfate was added to deionized water and mixed to form an ammonium sulfate concentration of 30 g / L of the additive solution; the base liquid and the additive solution were mixed in a ratio of 10:3 by volume to form a synthetic solution, reacted at room temperature for 15 hours, the solid phase product was filtered, washed with deionized water, and dried at room temperature for 11 hours to obtain a solid reactant polyindole-3 carbonyl formamide;
[0067] a2. Add polyindole-3-carbonylformamide, 5-indolecarboxylic acid, ammonium persulfate and ferric acetate to deionized water, mix to form an electrodeposition solution (polyindole-3-carbonylformamide added in an amount of 120 g, 5-indolecarboxylic acid added in an amount of 25 g, ammonium persulfate added in an amount of 15 g, and ferric acetate added in an amount of 40 g per liter of the electrodeposition solution), disperse with ultrasound for 1 hour, immerse the foamed iron sample in the electrodeposition solution and use it as a cathode (the weight of the foamed iron immersed in the electrodeposition solution per liter is 115 g), use a stainless steel electrode as an anode, and electrodeposit at a constant voltage of -1.3 V for 50 minutes at room temperature to obtain a foamed iron with polyindole-3-carbonylformamide on its surface, which is recorded as intermediate A.
[0068] Step [2] synthesizing polybis(trifluoromethylstyrene), specifically comprising the following operations:
[0069] b1. 3,5-bis(trifluoromethyl)styrene was added to dimethyl sulfoxide and mixed to form a reaction solution, wherein 120 g of 3,5-bis(trifluoromethyl)styrene was added per liter of the reaction solution; titanocene dichloride and lauroyl peroxide were added to chloroform and mixed to form a catalyst solution, wherein 12 g of titanocene dichloride and 5 g of lauroyl peroxide were added per liter of the catalyst solution;
[0070] b2. A certain amount of catalyst liquid was added to the reaction liquid (the volume ratio between the catalyst liquid and the reaction liquid was 4:13), and the reaction was carried out at room temperature for 25 hours. The solid phase product was filtered, washed with acetone and then with deionized water, and dried at room temperature for 9 hours to obtain poly(trifluoromethylstyrene).
[0071] Step [3] converting the polyindole-3-carbonylformamide on the surface of the foamed iron substrate into polyindole-3-carbonylformamide / poly(trifluoromethylstyrene) specifically comprises the following operations:
[0072] c1. The ammonium bifluoride and the poly(trifluoromethylstyrene) are added to deionized water and mixed to form a polymer forming liquid, wherein the amount of ammonium bifluoride added per liter of the polymer forming liquid is 40 g and the amount of poly(trifluoromethylstyrene) added is 110 g;
[0073] c2. The intermediate A is immersed in the polymer forming liquid (the weight of the intermediate A immersed in each liter of the polymer forming liquid is 70g), heated to 50°C in a water bath, reacted for 26 hours, and the foamed iron sample is taken out, dried at room temperature and under the protection of a nitrogen atmosphere for 5 hours to obtain a foamed iron with polyindole-3-carbonylformamide / polybis(trifluoromethylstyrene) loaded on the surface, i.e., the photocatalytic degradation material (foamed iron-based polyindole-3-carbonylformamide / polybis(trifluoromethylstyrene), recorded as Comparative Example 2. Among them, the reaction involved in this step is (hydrogen bonding between the imino group of polyindole-3-carbonylformamide and the fluoride ion of polybis(trifluoromethylstyrene):
[0074]
[0075] In order to analyze the performance of Example 1, Comparative Example 1 and Comparative Example 2 in photocatalytic degradation of acidic chrome blue K wastewater, acidic chrome blue K was added to deionized water to form simulated acidic chrome blue K wastewater with an acidic chrome blue K concentration of 40 mg / L. 100 ml of simulated acidic chrome blue K wastewater was poured into beakers respectively, and 20 g of Example 1, Comparative Example 1 and Comparative Example 2 were placed into beakers respectively. At the same time, 300 W xenon lamp light source ultraviolet light (λ = 280 nm) and visible light (λ = 550 nm) were used to irradiate Comparative Example 1, Comparative Example 2 and Example 1 for 80 minutes. The residual acidic chrome blue K concentration of the acidic chrome blue K wastewater after visible light catalytic degradation and ultraviolet light catalytic degradation was measured using an ultraviolet-visible spectrophotometer. The results are as follows: Figure 3As shown in the figure, it can be seen that the relative concentrations of residual acidic chrome blue K in Example 1 by visible light catalytic degradation and ultraviolet light catalytic degradation are only 0.08 and 0.04, respectively, while the relative concentrations of residual acidic chrome blue K in Comparative Example 1 by visible light catalytic degradation and ultraviolet light catalytic degradation are as high as 0.82 and 0.79, respectively, and the relative concentrations of residual acidic chrome blue K in Comparative Example 2 by visible light catalytic degradation and ultraviolet light catalytic degradation are 0.34 and 0.31, respectively. Obviously, Example 1 has high efficiency and excellent performance in photocatalytic degradation of acidic chrome blue K wastewater. Under the above-mentioned visible light and ultraviolet light treatment conditions and treatment time, Example 1, Comparative Example 1 and Comparative Example 2 are repeatedly used, and the relationship between the number of uses and the relative concentration of residual acidic chrome blue K is as follows: Figure 4 and Figure 5 As shown, it can be seen from the figure that when Example 1 is repeatedly recycled for the fifth time, its visible light catalytic degradation and ultraviolet light catalytic degradation rates of simulated acidic chrome blue K-containing wastewater still reach 90% (the relative concentration of residual acidic chrome blue K does not exceed 10%). Obviously, Example 1 has stable and efficient reusability.
[0076] In summary, the photocatalytic degradation material prepared according to the present invention has high-efficiency and excellent photocatalytic performance, and has excellent repeated use stability, and can meet the actual requirements of photocatalytic degradation of acidic chrome blue K wastewater.
[0077] To illustrate in further detail, three additional examples are provided below.
[0078] Example 2
[0079] Preferred embodiment 2 of the present invention provides a method for preparing a photocatalytic degradation material for treating acidic chrome blue K wastewater, comprising the following steps:
[0080] Step [1] loading polyindole-3-carbonylformamide on the surface of the foamed iron matrix specifically comprises the following operations:
[0081] a1. Indole-3-carboxylic acid methyl ester, 1H-indole-3-carboxamide and tert-butyl perbenzoate were added to dimethyl sulfoxide and mixed to form a base solution, wherein the amount of indole-3-carboxylic acid methyl ester added per liter of the base solution was 40 g, 1H-indole-3-carboxamide was added in an amount of 110 g, and tert-butyl perbenzoate was added in an amount of 5 mL; ammonium persulfate was added to deionized water and mixed to form an ammonium sulfate concentration of 20 g / L of the additive solution; the base liquid and the additive solution were mixed in a ratio of 8:1 between the volume ratio of the base liquid and the additive solution to form a synthetic solution, reacted at room temperature for 14 hours, the solid phase product was filtered, washed with deionized water, and dried at room temperature for 10 hours to obtain a solid reactant polyindole-3 carbonyl formamide;
[0082] a2. Add polyindole-3-carbonylformamide, 5-indolecarboxylic acid, ammonium persulfate and ferric acetate to deionized water and mix to form an electrodeposition solution (the amount of polyindole-3-carbonylformamide added per liter of the electrodeposition solution is 110 g, the amount of 5-indolecarboxylic acid added is 40 g, the amount of ammonium persulfate added is 5 g, and the amount of ferric acetate added is 30 g), and ultrasonic dispersion is used for 1 hour. The foamed iron sample is immersed in the electrodeposition solution and used as a cathode (the weight of the foamed iron immersed in the electrodeposition solution per liter is 110 g), a stainless steel electrode is used as an anode, and electrodeposition is carried out at a constant voltage of -1.0 V for 60 minutes at room temperature to obtain a foamed iron loaded with polyindole-3-carbonylformamide on the surface, which is recorded as intermediate A.
[0083] Step [2] synthesizing polybis(trifluoromethylstyrene), specifically comprising the following operations:
[0084] b1. 3,5-bis(trifluoromethyl)styrene was added to dimethyl sulfoxide and mixed to form a reaction solution, wherein 90 g of 3,5-bis(trifluoromethyl)styrene was added per liter of the reaction solution; titanocene dichloride and lauroyl peroxide were added to chloroform and mixed to form a catalyst solution, wherein 5 g of titanocene dichloride and 8 g of lauroyl peroxide were added per liter of the catalyst solution;
[0085] b2. A certain amount of catalyst liquid was added to the reaction liquid (the volume ratio between the catalyst liquid and the reaction liquid was 2:13), and the reaction was carried out at room temperature for 24 hours. The solid phase product was filtered, washed with acetone and then with deionized water, and dried at room temperature for 8 hours to obtain poly(trifluoromethylstyrene).
[0086] Step [3] converting the polyindole-3-carbonylformamide on the surface of the foamed iron substrate into a polyindole-3-carbonylformamide / poly(trifluoromethylstyrene) cobalt coordination polymer, specifically comprising the following operations:
[0087] c1. Adding cobalt bromide, urea, ammonium bifluoride and the polybis(trifluoromethyl)styrene to deionized water, mixing to form a coordination polymer solution, wherein the amount of cobalt bromide added per liter of the coordination polymer solution is 150 g, the amount of urea added is 45 g, the amount of ammonium bifluoride added is 20 g, and the amount of polybis(trifluoromethyl)styrene added is 130 g;
[0088] c2. Immerse the intermediate A in the coordination polymer forming liquid (the weight of the intermediate A immersed in each liter of the coordination polymer forming liquid is 60g), heat it to 60°C in a water bath, react for 24 hours, take out the foamed iron sample, and dry it at room temperature under the protection of a nitrogen atmosphere for 4 hours to obtain foamed iron with a surface loaded with polyindole-3-carbonylformamide / polybis(trifluoromethylstyrene) cobalt coordination polymer, i.e., the photocatalytic degradation material (foamed iron-based polyindole-3-carbonylformamide / polybis(trifluoromethylstyrene) cobalt coordination polymer).
[0089] Example 3
[0090] Preferred embodiment 3 of the present invention provides a method for preparing a photocatalytic degradation material for treating acidic chrome blue K wastewater, comprising the following steps:
[0091] Step [1] loading polyindole-3-carbonylformamide on the surface of the foamed iron matrix specifically comprises the following operations:
[0092] a1. Indole-3-carboxylic acid methyl ester, 1H-indole-3-carboxamide and tert-butyl perbenzoate were added to dimethyl sulfoxide and mixed to form a base solution, wherein the amount of indole-3-carboxylic acid methyl ester added per liter of the base solution was 70 g, 1H-indole-3-carboxamide was added in an amount of 80 g, and tert-butyl perbenzoate was added in an amount of 30 mL; ammonium persulfate was added to deionized water and mixed to form an ammonium sulfate concentration of 40 g / L of the additive solution; the base liquid and the additive solution were mixed in a ratio of 11:3 by volume to form a synthetic solution, reacted at room temperature for 18 hours, the solid product was filtered, washed with deionized water, and dried at room temperature for 12 hours to obtain a solid reactant polyindole-3 carbonyl formamide;
[0093] a2. Add polyindole-3-carbonylformamide, 5-indolecarboxylic acid, ammonium persulfate and ferric acetate to deionized water, mix to form an electrodeposition solution (polyindole-3-carbonylformamide added in an amount of 140 g, 5-indolecarboxylic acid added in an amount of 20 g, ammonium persulfate added in an amount of 20 g, and ferric acetate added in an amount of 60 g per liter of the electrodeposition solution), disperse with ultrasonic wave for 0.5 hour, immerse the foamed iron sample in the electrodeposition solution and use it as a cathode (the weight of the foamed iron immersed in the electrodeposition solution per liter is 140 g), use a stainless steel electrode as an anode, and electrodeposit at a constant voltage of -1.5 V for 40 minutes at room temperature to obtain a foamed iron with polyindole-3-carbonylformamide on its surface, which is recorded as intermediate A.
[0094] Step [2] synthesizing polybis(trifluoromethylstyrene), specifically comprising the following operations:
[0095] b1. 3,5-bis(trifluoromethyl)styrene was added to dimethyl sulfoxide and mixed to form a reaction solution, wherein 3,5-bis(trifluoromethyl)styrene was added in an amount of 130 g per liter of the reaction solution; dichlorotitacenene and lauroyl peroxide were added to chloroform and mixed to form a catalyst solution, wherein dichlorotitacenene was added in an amount of 15 g and lauroyl peroxide was added in an amount of 2 g per liter of the catalyst solution;
[0096] b2. A certain amount of catalyst liquid was added to the reaction liquid (the volume ratio between the catalyst liquid and the reaction liquid was 5:19), and the reaction was carried out at room temperature for 28 hours. The solid phase product was filtered, washed with acetone and then with deionized water, and dried at room temperature for 10 hours to obtain poly(trifluoromethylstyrene).
[0097] Step [3] converting the polyindole-3-carbonylformamide on the surface of the foamed iron substrate into a polyindole-3-carbonylformamide / poly(trifluoromethylstyrene) cobalt coordination polymer, specifically comprising the following operations:
[0098] c1. Adding cobalt bromide, urea, ammonium bifluoride and the polybis(trifluoromethylstyrene) to deionized water, mixing to form a coordination polymer solution, wherein the amount of cobalt bromide added per liter of the coordination polymer solution is 190 g, the amount of urea added is 30 g, the amount of ammonium bifluoride added is 70 g, and the amount of polybis(trifluoromethylstyrene) added is 80 g;
[0099] c2. Immerse the intermediate A in the coordination polymer forming liquid (the weight of the intermediate A immersed in each liter of the coordination polymer forming liquid is 90g), heat it to 40°C in a water bath, react for 30 hours, take out the foamed iron sample, and dry it at room temperature under the protection of a nitrogen atmosphere for 6 hours to obtain foamed iron with a surface loaded with polyindole-3-carbonylformamide / polybis(trifluoromethylstyrene) cobalt coordination polymer, i.e., the photocatalytic degradation material (foamed iron-based polyindole-3-carbonylformamide / polybis(trifluoromethylstyrene) cobalt coordination polymer).
[0100] Example 4
[0101] Preferred embodiment 4 of the present invention provides a method for preparing a photocatalytic degradation material for treating acidic chrome blue K wastewater, comprising the following steps:
[0102] Step [1] loading polyindole-3-carbonylformamide on the surface of the foamed iron matrix specifically comprises the following operations:
[0103] a1. Indole-3-carboxylic acid methyl ester, 1H-indole-3-carboxamide and tert-butyl perbenzoate were added to dimethyl sulfoxide and mixed to form a base solution, wherein the amount of indole-3-carboxylic acid methyl ester added per liter of the base solution was 55 g, 1H-indole-3-carboxamide was added in an amount of 95 g, and tert-butyl perbenzoate was added in an amount of 20 mL; ammonium persulfate was added to deionized water and mixed to form an ammonium sulfate concentration of 30 g / L of the additive solution; the base liquid and the additive solution were mixed in a ratio of 9:2 in a volume ratio to form a synthetic solution, reacted at room temperature for 16 hours, the solid phase product was filtered, washed with deionized water, and dried at room temperature for 11 hours to obtain a solid reactant polyindole-3 carbonyl formamide;
[0104] a2. Add polyindole-3-carbonylformamide, 5-indolecarboxylic acid, ammonium persulfate and ferric acetate to deionized water, mix to form an electrodeposition solution (polyindole-3-carbonylformamide added in an amount of 125 g, 5-indolecarboxylic acid added in an amount of 30 g, ammonium persulfate added in an amount of 12 g, and ferric acetate added in an amount of 45 g per liter of the electrodeposition solution), disperse with ultrasound for 0.9 hour, immerse the foamed iron sample in the electrodeposition solution and use it as a cathode (the weight of the foamed iron immersed in the electrodeposition solution per liter is 125 g), use a stainless steel electrode as an anode, and electrodeposit at a constant voltage of -1.2 V for 50 minutes at room temperature to obtain a foamed iron with polyindole-3-carbonylformamide on its surface, which is recorded as intermediate A.
[0105] Step [2] synthesizing polybis(trifluoromethylstyrene), specifically comprising the following operations:
[0106] b1. 3,5-bis(trifluoromethyl)styrene was added to dimethyl sulfoxide and mixed to form a reaction solution, wherein 3,5-bis(trifluoromethyl)styrene was added in an amount of 110 g per liter of the reaction solution; titanocene dichloride and lauroyl peroxide were added to chloroform and mixed to form a catalyst solution, wherein titanocene dichloride was added in an amount of 10 g and lauroyl peroxide was added in an amount of 5 g per liter of the catalyst solution;
[0107] b2. A certain amount of catalyst liquid was added to the reaction liquid (the volume ratio between the catalyst liquid and the reaction liquid was 4:15), and the reaction was carried out at room temperature for 26 hours. The solid phase product was filtered, washed with acetone and then with deionized water, and dried at room temperature for 9 hours to obtain poly(trifluoromethylstyrene).
[0108] Step [3] converting the polyindole-3-carbonylformamide on the surface of the foamed iron substrate into a polyindole-3-carbonylformamide / poly(trifluoromethylstyrene) cobalt coordination polymer, specifically comprising the following operations:
[0109] c1. Adding cobalt bromide, urea, ammonium bifluoride and the polybis(trifluoromethylstyrene) to deionized water, mixing to form a coordination polymer solution, wherein the amount of cobalt bromide added per liter of the coordination polymer solution is 170 g, the amount of urea added is 36 g, the amount of ammonium bifluoride added is 45 g, and the amount of polybis(trifluoromethylstyrene) added is 105 g;
[0110] c2. Immerse the intermediate A in the coordination polymer forming liquid (the weight of the intermediate A immersed in each liter of the coordination polymer forming liquid is 75g), heat it to 50°C in a water bath, react for 26 hours, take out the foamed iron sample, and dry it at room temperature and under the protection of a nitrogen atmosphere for 5 hours to obtain foamed iron with a surface loaded with polyindole-3-carbonylformamide / polybis(trifluoromethylstyrene) cobalt coordination polymer, i.e., the photocatalytic degradation material (foamed iron-based polyindole-3-carbonylformamide / polybis(trifluoromethylstyrene) cobalt coordination polymer).
[0111] The above are only preferred embodiments of the present invention. It should be understood that the description of the above embodiments is only used to help understand the method and core ideas of the present invention, and is not used to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, etc. made within the ideas and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a photocatalytic degradation material for treating acidic chrome blue K wastewater, characterized in that: The following steps are included: Step [1]: loading polyindole-3-carbonylformamide on the surface of the foamed iron matrix; Step [2] synthesizing poly(trifluoromethylstyrene); Step [3] converts the polyindole-3-carbonylformamide on the surface of the foamed iron matrix into a polyindole-3-carbonylformamide / poly(trifluoromethylstyrene) cobalt coordination polymer.
2. The method for preparing a photocatalytic degradation material for treating acidic chrome blue K wastewater according to claim 1, characterized in that: The step [1] specifically includes the following operations: a1. Add indole-3-carboxylic acid methyl ester, 1H-indole-3-carboxamide and tert-butyl peroxybenzoate to dimethyl sulfoxide and mix to form a base solution; add ammonium persulfate to deionized water and mix to form an additive solution; mix the base solution and the additive solution in a certain proportion to form a synthetic solution, react at room temperature for 14 to 18 hours, filter the solid product, wash with deionized water, and dry at room temperature for 10 to 12 hours to obtain a solid reactant polyindole-3 carbonyl formamide; a2. Add polyindole-3-carbonylformamide, 5-indolecarboxylic acid, ammonium persulfate and ferric acetate to deionized water, mix to form an electrodeposition solution, disperse by ultrasonic wave for 0.5 to 1 hour, immerse the foamed iron sample in the electrodeposition solution and use it as cathode, use stainless steel electrode as anode, and electrodeposit at room temperature at a constant voltage of -1.0V to -1.5V for 40 to 60 minutes to obtain foamed iron with polyindole-3-carbonylformamide loaded on the surface, which is recorded as intermediate A.
3. The method for preparing a photocatalytic degradation material for treating acidic chrome blue K wastewater according to claim 2, characterized in that: In step a1, the amount of indole-3-carboxylic acid methyl ester added to each liter of the base liquid is 40-70 g, the amount of 1H-indole-3-carboxamide added is 80-110 g, and the amount of tert-butyl peroxybenzoate added is 5-30 mL; the concentration of ammonium persulfate in the additive liquid is 20-40 g / L; and the volume ratio between the base liquid and the additive liquid in the synthetic liquid is 8-11:1-3.
4. The method for preparing a photocatalytic degradation material for treating acidic chrome blue K wastewater according to claim 2, characterized in that: In step a2, the amount of polyindole-3-carbonylformamide added to each liter of the electrodeposition solution is 110-140 g, the amount of 5-indolecarboxylic acid added is 20-40 g, the amount of ammonium persulfate added is 5-20 g, and the amount of ferric acetate added is 30-60 g; the weight of the foamed iron immersed in each liter of the electrodeposition solution is 110-140 g.
5. The method for preparing a photocatalytic degradation material for treating acidic chrome blue K wastewater according to claim 1, characterized in that: The step [2] specifically includes the following operations: b1. Add 3,5-bis(trifluoromethyl)styrene to dimethyl sulfoxide and mix to form a reaction solution; add titanocene dichloride and lauroyl peroxide to chloroform and mix to form a catalyst solution; b2. Add a certain amount of catalyst liquid to the reaction solution, react at room temperature for 24-28 hours, filter the solid phase product, wash with acetone and then with deionized water, and dry at room temperature for 8-10 hours to obtain poly(trifluoromethylstyrene).
6. The method for preparing a photocatalytic degradation material for treating acidic chrome blue K wastewater according to claim 5, characterized in that: In step b1, the amount of 3,5-bis(trifluoromethyl)styrene added to each liter of the reaction solution is 90-130 g; the amount of titanocene dichloride added to each liter of the catalyst solution is 5-15 g, and the amount of lauroyl peroxide added to each liter of the catalyst solution is 2-8 g.
7. The method for preparing a photocatalytic degradation material for treating acidic chrome blue K wastewater according to claim 5, characterized in that: In step b2, the volume ratio between the catalytic liquid and the reaction liquid is 2-5:13-19.
8. The method for preparing a photocatalytic degradation material for treating acidic chrome blue K wastewater according to claim 1, characterized in that: The step [3] specifically includes the following operations: c1. Adding cobalt bromide, urea, ammonium bifluoride and the poly(trifluoromethylstyrene) to deionized water and mixing to form a coordination polymer solution; c2. Immerse the intermediate A in the coordination polymer formation liquid, heat it in a water bath to 40-60°C, react for 24-30 hours, take out the foamed iron sample, and dry it for 4-6 hours at room temperature under the protection of a nitrogen atmosphere to obtain a foamed iron with a surface loaded with polyindole-3-carbonylformamide / polybis(trifluoromethylstyrene) cobalt coordination polymer, i.e., the photocatalytic degradation material.
9. The method for preparing a photocatalytic degradation material for treating acidic chrome blue K wastewater according to claim 8, characterized in that: In step c1, per liter of the coordination polymer forming liquid, the amount of cobalt bromide added is 150-190 g, the amount of urea added is 30-45 g, the amount of ammonium bifluoride added is 20-70 g, and the amount of polybis(trifluoromethylstyrene) added is 80-130 g.
10. The method for preparing a photocatalytic degradation material for treating acidic chrome blue K wastewater according to claim 8, characterized in that: In step c2, the weight of the intermediate A immersed in each liter of the coordination polymer forming liquid is 60-90 g.
Citation Information
Patent Citations
Preparation method of Cp*Co(CO)I2-loaded cobalt-doped zinc oxide photoanode nano array
CN110528023A
Three-dimensional covalent organic framework lithium salt containing polyhedral oligomeric silsesquioxane as well as preparation method and application of three-dimensional covalent organic framework lithium salt
CN116284631A
Three-dimensional foam-based photocatalytic material for efficiently removing composite pollutants in water as well as preparation method and application of three-dimensional foam-based photocatalytic material
CN116422333A
Preparation method of catalytic degradation agent for treating phenolic wastewater by ultrasonic synergistic Fenton
CN118681598A
Photocatalytic oil-water separation material and preparation method thereof
US20220184590A1